ANALYSIS OF INTEGRATION AND PRICE EFFICIENCY: A CASE OF INDONESIAN COCOA BEANS EXPORT MARKET - Imama Nurus Izaati; Ratya Anindita; S Sujarwo (Socio-Economics/Agribusiness Department, 2020)
In international trade, two market are spatially integrated when the price of one commodity traded continuously and has same price movement after adjusting the exchange rate and transaction cost. This condition indicate that price eficiency because information of price is well spread, so no participant of market can manipulate price. Price movement of Indonesian cocoa beans has different movement with price of world market and importing countries. This indicate no price transmission, which means there is price discrepancy of Indonesia with world market and importing countries. This study examined degree of integration and price efficiency of Indonesia cocoa beans with world market and importing countries. Integration analysis using Cointegration Johansen approach, Vector Autoregression (VAR)/Vector Error Correction Model (VECM) and price efficiency analysis using the Generalized Autoregeressive Conditional Heteroscedasticity (GARCH) approach . The results showed that the price of Indonesian cocoa beans integrates long term with the price of cocoa beans in the world market (New York Board of Trade) and India. In the short term price of Indonesian cocoa beans integrated with the price of cocoa beans in Malaysia. Among the prices of Indonesian cocoa beans with USA does not happen both long-term and short-term integration. The price of Indonesian cocoa beans in the spot market of Makassar is included in the efficient market category of weak forms, where the current price reflects a set of pricing information in the past.